Social Classification in Sports: A Literature Review on Access, Identity, and Social Mobility - Chikitania Larasuria Maronji; Padli Padli; Eri Barlian (Jurnal Patriot, 2026)
Problems: Previous studies indicate that sports participation is strongly influenced by socioeconomic factors; however, comprehensive analyses that integrate access, identity formation, and social mobility within the context of social classification remain limited, particularly in sports sociology literature. This gap highlights the need for a systematic review that critically examines sports as both a space of inequality and opportunity, thereby offering novelty through an integrative and theory-driven perspective. Purpose: This study aims to analyze how social classification shapes access to sports participation, constructs social identity, and enables or constrains social mobility through sports. Methods: This research employed a qualitative approach using library research methods. Data were collected from national and international peer-reviewed journals indexed in reputable databases and published between 2018 and 2024. The selected literature was analyzed thematically using content analysis to identify patterns related to access inequality, identity construction, and social mobility in sports. Results: The findings show that socioeconomic background significantly determines access to sports facilities, professional coaching, and institutional support, with higher social classes enjoying greater advantages. Sports also function as symbols of social identity and class distinction, reflecting processes of social reproduction. At the same time, sports provide opportunities for upward social mobility, particularly for individuals from economically disadvantaged backgrounds through scholarships, sponsorships, and athletic achievement. However, these opportunities are limited by persistent structural barriers, including unequal resource distribution, gender bias, and selective policy implementation. Conclusion: This study concludes that sports both reflect and reproduce broader social stratification while simultaneously offering selective pathways for social mobility. The findings contribute theoretically to sports sociology and practically to sports education policy, emphasizing the need for more inclusive and equitable approaches. Future research is recommended to incorporate empirical field studies and comparative regional analyses to deepen understanding of social inequality in sports.